Ascitic fluid due to type II herpes simplex virus infection: Report of a case with immunocytochemical confirmation. Issue 4 (27th January 2012) - Yoshida, Keiko; Miyahira, Yoshimitsu; Ishida, Mitsuaki; Iwai, Muneo; Kagotani, Akiko; Arita, Namie; Iwamoto, Nozomi; Takikita, Mikiko; Kojima, Fumiyoshi; Okabe, Hidetoshi
Abstract Herpes simplex virus (HSV) infection is usually observed in the oral cavity and external genitals, and HSV peritonitis is extremely rare. Herein, we report a case of type II HSV peritonitis successfully diagnosed by ascitic cytology. A 66‐year‐old Japanese man, who had been treated with steroid inhalation for 5 years due to chronic obstructive pulmonary disease, was suspected to have acute cholecystitis. Laparoscopic cholecystectomy and intraoperative cytological examination of ascitic fluid were performed. Cytological study of ascitic fluid revealed that abundant granular cell debris, degenerative cells and apoptotic bodies were present, as well as some single or multinucleated cells with ground glass nuclei. However, vivid mesothelial cells were rarely seen. Immunocytochemical staining for type II HSV was positive in single or multinucleated cells with ground glass nuclei. Therefore, a diagnosis of type II HSV peritonitis was made. This is the first reported case of type II HSV peritonitis successfully diagnosed by ascitic cytology. This report highlights that the presence of abundant cell debris, degenerative cells and apoptotic bodies, and the absence of vivid mesothelial cells are the key cytological findings to suspect HSV peritonitis, and the diagnosis can be confirmed by careful surveillance for characteristic nuclear findings of single or multinucleated cells. The frequency of opportunistic infection is increased because of the increased numbers of iatrogenic immunocompromised patients as seen in this case, therefore, cytological examination is a useful method for early detection of the causative agent of peritonitis including HSV. Diagn. Cytopathol. 2013;41:354–359. © 2011 Wiley Periodicals, Inc.